SAND MANAGEMENT APPROACH FOR A FIELD WITH HIGH VISCOSITY OIL - Tananykhin, Dmitry Sergeevich; Grigorev, Maxim Borisovich; Poroshin, Maksim Aleksandrovich (Journal of Applied Engineering Science, 2020)
Oil production from weakly consolidated sandstone wasn’t needed for decades, but as the time goes on, traditional oil reserves deplete and possibility of these reserves being produced is growing up. In the case of high viscosity oil, located in such reservoir, problem gets even worse. Traditional sand control methods cause lower production rates, thus, making production not profitable enough. In the industry there was need for new approach and it appeared – sand management. Sand management is a risky business, but it allows some reservoirs to be produced with good enough profit. But with right amount of preparations risk can be minimized and production becomes more likely. One of the most promising instruments of sand management is chemical treatment with UTTA. It allows to sand particles and fines to be held in the reservoir so they won’t cause so much erosion and won’t plug pore throats and filtration channels.